Assessment of effectiveness of an interventional package on treatment adherence of hypertensive patients: a randomized control trial - Nongspung, Kmendalin; Narang, Kavita; Thakur, Jarnail Singh (International Journal Of Community Medicine And Public Health, 2021)
Background: Hypertension is the most common non-communicable diseases. Strict adherence to prescribed antihypertensive treatments is the key to blood pressure control. The present study was conducted with the objective to develop, implement and assess an interventional package on treatment adherence for hypertensive patients. Methods: A clustered randomized control trial of 3 months conducted in two community sites of Chandigarh. The two sites were first randomized by lottery method as experimental and control sites. Total of 250 subjects (n=125 on each sites) were selected by a systematic random sampling technique (every fourth) from the sampling frame. Diagnosed hypertensive patients taking treatment were included in the study and females with pregnancy induced hypertension were excluded. Participants were interviewed as per Interview schedule. Data was collected from July to November 2018. Interventional package was in the form of booklet and flash card, delivered as one to one teachings. Total of 5 face to face follow ups were done to the experimental group. Control group received routine care. Final evaluation was done at 3rd month in both the groups to assess the effectiveness of an interventional package on treatment adherence. Data analysis and interpretation was done by using chi square, paired t test, unpaired t- test, Mc Nemar test were applied to determine the level of significance at p<0.05. Results: The proportion of subjects who were adhered to the treatment has increased from 16% to 68% in the experimental group at third month of follow up. The mean change in systolic blood pressure and diastolic blood pressure were 26.29±12.81 mmHg and 7.74±8.95 mmHg respectively in the experimental group as compared to the control group (p<0.05). Conclusions: The interventional package on treatment adherence among hypertensive patients was effective in improving the treatment adherence.